Measuring inflation persistence: a structural time series approach - Maarten Dossche; Gerdie Everaert (European Central Bank (ECB), 2005)
Time series estimates of inflation persistence incur an upward bias if shifts in the inflation target of the central bank remain unaccounted for. Using a structural time series approach we measure different sorts of inflation persistence allowing for an unobserved time-varying inflation target. Unobserved components are identified using Kalman filtering and smoothing techniques. Posterior densities of the model parameters and the unobserved components are obtained in a Bayesian framework based on importance sampling. We find that inflation persistence, expressed by the half-life of a shock, can range from 1 quarter in case of a cost-push shock to several years for a shock to long-run inflation expectations or the output gap.
Keywords: C11; C13; C22; C32; E31; 330; Bayesian Analysis; Inflation persistence; inflation target; Kalman filter; Inflation; Schätzung; Zustandsraummodell